INTERPRETASI MUHAMMAD IQBAL TENTANG ATOMISME DALAM KALAMASY'ARIYAH - Muzairi Muzairi (UIN Sunan Kalijaga Yogyakarta, 2015)
According Iqbalin The Reconstruction ofReligious Thought in Islam theAsy'arie school, of thinkers, then, the world is compounded of what they calljawahir-infinitely small parts of atoms which can-not be further divided. Since the creative activity of God is ceaseless the number of the atoms cannot be finite. Fresh atoms are coming into being every moment, and the universe is therefore constantly growing. As the Quran says: